Studies of genetic distance and gene flow in Red Sokoto and West African Dwarf goats using restriction fragment length polymorphic marker - Tella, Adetunmbi; Dandara, Gazali Bala; Osunkeye, Olumuyiwa Jacob; Adebayo, Francis Bosede; Gabriel, Godfrey Odey (Acta Scientiarum. Animal Sciences, 2025)
Due to their hardiness in severe weather, capability to yield milk and meat, fast generation times, capacity to withstand the substandard diets, goats constitute an indispensable part of rural agricultural systems. Gene flow, genetic distance, and alleles were investigated in Red Sokoto (50) and West African Dwarf (45). For each animal, approximately 5 milliliters of aseptic blood taken. Restriction fragment length polymorphism and electrophoresis were carried out after the DNA samples were isolated and purified. Gene flow, anticipated (He) and observed heterozygosity (Ho), degree of genetic diversity and Hardy-Weinberg equilibrium (HWE) were determined. The results revealed that for Red Sokoto and West African Dwarf goats, the allele frequency of gene A and C varied between (7.2 &7.5) and (2.8 & 2.4) respectively. Ho values were 56% for Red Sokoto and 48.89% for West African Dwarf. The West African dwarf (37.35%) had the lowest estimates of He compared to Red Sokoto population (40.73%).The Mean Fis, Fit, Fst and Nm* were -0.3576, -0.3554, 0.0016 and 152.78 respectively for the populations studied. According to the findings, the goat populations exhibited the highest genetic similarity (0.9996) and the lowest genetic distance (0.0004), It was deduced that there is homology of alleles at the locus, low percentage of gene differentiation, and heterozygosis loss in the populations of native goats studied.